Towards a pharmacochemical hypothesis of the prophylaxis of SARS-CoV-2 by psychoactive substances. (November 2020) - Javelot, Hervé; Petrignet, Julien; Addiego, Frédéric; Briet, Jeanne; Solis, Morgane; El-Hage, Wissam; Hingray, Coraline; Weiner, Luisa
Abstract: An increasing body of evidence suggests a protective effect of some psychoactive substances against SARS-CoV-2 (Severe Acute Respiratory Syndrome coronavirus type 2). Recent findings suggest that patients with psychiatric disorders are less affected by SARS-CoV-2 than their caregivers, which may seem surprising given some of the frequent risk factors for an unfavorable course of the disease (e.g., obesity, diabetes, cardiovascular and pulmonary diseases). We propose here a mixed pharmacoepidemiological and pharmacochemical hypothesis to explain these findings. A number of psychotropic drugs exhibit activities against coronaviruses (Middle East Respiratory Syndrome coronavirus (MERS-CoV), the Severe Acute Respiratory Syndrome coronavirus (SARS-CoV-1) and the Infectious Bronchitis Virus (IBV)) and have been put forward as potentially anti-SARS-CoV-2. These treatments include numerous mee-too drugs (chemically and pharmacologically linked to those which have demonstrated anti-SARS-CoV-2 efficacy) which are frequently prescribed in psychiatric settings. Taken alone or in polypharmacy, these drugs could have a prophylactic anti-SARS-CoV-2 effect, explaining the unexpectedly low proportion of patients with psychiatric disorders and COVID-19. Associated factors such as nicotine can also be considered in the context of a broad chemoprophylactic hypothesis in patients with psychiatric disorders taking different psychoactive substances.